Hasidism key questions - Wodziński, Marcin 1966- (Oxford University Press, 2018)
"By combining some oldest questions with new sources and methodologies, Hasidism: Key Questions provides a refreshingly new look at many central issues in historiography of Hasidism: its definition, gender, leadership, demographic size, geography, economy, and decline. This is the first such attempt to respond those central questions in one book"...
Includes bibliographical references and index
Keywords: Geschichte; Hasidism -- Historiography; Chassidismus; Ostmitteleuropa